The technology adoption process in subsistence agriculture: the case of cassava in southwestern Nigeria - Polson, R.; Spencer, D. (Elsevier, 1991)
The adoption decisions of subsistence multicrop producers regarding improved cassava variety (TMS 30572) in the humid tropical rainforest ecology of Southwestern Nigeria were analysed within a qualitative choice framework. The empirical results revealed that younger farmers producing marketable surpluses on holdings in excess of the mean farm size of 0·6 ha exhibited higher propensities of adopting TMS 30572 compared with farmers producing primarily for household consumption. The activities of extension agents among subsistence producers were statistically significant in the technology adoption process. Migrant farmers were identified as early adopters by the empirical model. These results have significant implications for extension personnel, research scientists and policymakers, and provide further justification for strengthening the extension capacities of the national research programs within the cassava belt of the humid forest ecologies of West and Central Africa.